The Cost of Blindness in the Republic of Ireland 2010–2020. (15th February 2016) - Green, D.; Ducorroy, G.; McElnea, E.; Naughton, A.; Skelly, A.; O'Neill, C.; Kenny, D.; Keegan, D.
Abstract : Aims . To estimate the prevalence of blindness in the Republic of Ireland and the associated financial and total economic cost between 2010 and 2020. Methods . Estimates for the prevalence of blindness in the Republic of Ireland were based on blindness registration data from the National Council for the Blind of Ireland. Estimates for the financial and total economic cost of blindness were based on the sum of direct and indirect healthcare and nonhealthcare costs. Results . We estimate that there were 12, 995 blind individuals in Ireland in 2010 and in 2020 there will be 17, 997. We estimate that the financial and total economic costs of blindness in the Republic of Ireland in 2010 were€ 276.6 million and€ 809 million, respectively, and will increase in 2020 to€ 367 million and€ 1.1 billion, respectively. Conclusions . Here, ninety-eight percent of the cost of blindness is borne by the Departments of Social Protection and Finance and not by the Department of Health as might initially be expected. Cost of illness studies should play a role in public policy making as they help to quantify the indirect or "hidden" costs of disability and so help to reveal the true cost of illness.